Local Renin-Angiotensin System in the Reproductive System - Herr, Daniel; Bekes, Inga; Wulff, Christine (Frontiers in Endocrinology, 2013)
The renin–angiotensin system (RAS) is well known as regulator of electrolytes and blood pressure. Besides this function, there are numerous studies supporting the idea of a local tissue RAS. This system controls the local activity of the different RAS family members, especially of the functional proteins Angiotensin II and Angiotensin (1-7). Those antagonistically acting proteins have been described to be expressed in different organ systems including the human reproductive tract. Therefore, this local RAS has been suspected to be involved in the control and regulation of physiological and pathological conditions in the female reproduction tract. This review of the available literature summarizes the physiological influence of the RAS on the follicular development, ovarian angiogenesis and placental- and uterine function. In addition, in the second part the role of the RAS concerning ovarian- and endometrial cancer becomes elucidated. This section includes possible novel therapeutic strategies via inhibition of RAS-mediated tumor growth and angiogenesis. Looking at a very complex system of agonistic and antagonistic tissue factors, it may be supposed that the RAS in the female reproduction tract will be of rising scientific interest in the upcoming years.